Pengenalan Karakteristik Gaya Belajar Siswa Korong Sijangek Kenagarian Sungai Durian Kecamatan Patamuan Kabupaten Padang Pariaman - Momon Dt. Tanamir; Nila Afryansih; Rozana Eka Putri; Revi Efendi; Mutia Ferina (RANGKIANG: Jurnal Pengabdian Pada Masyarakat, 2019)
Student learning styles can be interpreted as the preferred way for students to carry out activities of thinking, processing and understanding information and knowledge in learning. In the process of learning activities, each student has a method or style of learning that is different so that the learning outcomes obtained is varies. In general, the learning styles commonly used by students in the learning process are a combination of visual learning styles (sense of sight), auditive (sense of hearing) and kinesthetic (sense of touch). The introduction of the characteristics of learning styles so that students can know and understand the characteristics of their learning styles, make adjustments to learning methods that are suitable for absorbing science and technology in the learning process in the classroom as well as independent learning outside and at home. Parents of students also need to be given an understanding of the characteristics of their child’s learning styles so they don't make mistakes in disciplining children in learning and better understanding of their children's potential. For example children with dominant kinesthetic learning styles usually cannot stand sitting too long to listen to the teacher's instruction so that they do other activities such as permission and disturb their friends because they can learn better when accompanied by physical activities, as well as with other learning style characters. The results of this activity are satisfying, visible students enthusiastic in identifying learning styles and understanding methods of learning that are suitable and their potential and for parents are also enthusiastic in this activity because they are given direction in understanding their child’s learning styles and potential.